2019
DOI: 10.1038/s41586-019-1312-2
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding deletions reveal a gene that is critical for intestinal function

Abstract: Large-scale genome sequencing is poised to provide an exponential increase in the discovery of disease-associated mutations, but the functional interpretation of such mutations remains challenging. Here we identify deletions of a sequence termed intestine-critical region (ICR) on chromosome 16 that cause intractable congenital diarrhea in infants 1,2. Transgenic mouse reporter assays show that the ICR contains a regulatory sequence that activates transcription during development of the gastrointestinal system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The first is a TATA box mutation in UGT1A1 (NM_000463.2:c.-41_-40dupTA) [36]. The second is a deletion (chr16:1480850_1483950del) in a patient with unexplained diarrhea, and this deletion was reported very recently to be the cause of chronic diarrhea secondary to its regulatory effect on PERCC1 [37].…”
Section: Quantifying the Contribution Of Transcript-deleterious Variantsmentioning
confidence: 99%
“…The first is a TATA box mutation in UGT1A1 (NM_000463.2:c.-41_-40dupTA) [36]. The second is a deletion (chr16:1480850_1483950del) in a patient with unexplained diarrhea, and this deletion was reported very recently to be the cause of chronic diarrhea secondary to its regulatory effect on PERCC1 [37].…”
Section: Quantifying the Contribution Of Transcript-deleterious Variantsmentioning
confidence: 99%
“…In contrast to the well-established effects of coding variation, the impact of noncoding SVs on regulatory elements is mostly unknown. Examples of SVs with strong noncoding effects are scarce in humans and model organisms, [39][40][41] though recent studies have shown that noncoding SVs are relevant for gene regulation and disease. 42,43 We explored noncoding dosage sensitivity across a spectrum of 14 regulatory element classes, ranging from high-confidence experimentally validated enhancers to large databases of computationally predicted elements.…”
Section: Figure 3 | Genome-wide Mutational Patterns Of Svsmentioning
confidence: 99%
“…These studies may lead one to the interpretation that loss of an individual enhancer is not likely to produce strong phenotypic effects. However, it has been shown that alterations at single enhancers are linked to rare Mendelian diseases [23][24][25][26]. Thus, based on our current understanding, the phenotypic effects of enhancer LoF likely fall into a spectrum where deletion of LoF-tolerant enhancers would not elicit substantial phenotypic impact, while some enhancers are likely to cause fitness defects even when single enhancers exhibit LoF.…”
mentioning
confidence: 99%